AGRICULTURAL PRODUCTION OF CANNABIS AIMING TO INCREASE CANNABIDIOL (CBD) CONTENT FOR MEDICINAL PURPOSES – A REVIEW - Orsi, Valéria de Campos; da Silva, Larissa Rocha Camargo; Silva, Gabriela Rocha Vidal; Pasiani, Rafaela Orsi; Oshima-Franco, Yoko (Seven Editora, 2026)
Cannabis sativa Linnaeus is a herbaceous plant from the Cannabaceae family. Its female inflorescences are rich in glandular trichomes, which contain secondary metabolites with medicinal properties, such as cannabidiol (CBD). The lack of information on the cultivation management of Cannabis for biomedical purposes hinders the development of high-quality and standardized production. A literature search was conducted for studies involving interventions in Cannabis cultivation aimed at improving CBD content for medicinal purposes. A systematic search was performed in the CAPES Periodicals Portal > Collection > Subject >, using the search term "Cannabis and Crop Production," filtering for open-access, original, peer-reviewed articles in English. Scientific articles containing cultivation practices for Cannabis chemotype III relevant to the objective were included. The following were excluded: articles on agricultural production of Cannabis for non-medicinal purposes, review articles, non-scientific studies, THC > 0.3%, without CBD improvement, without instrumental analysis of CBD content, and Cannabis Chemotypes I and II. The search resulted in 9 eligible articles, with the following interventions: manipulation of phosphorus concentrations; sowing density and nitrogen fertilization; application of auxin antagonists under in vitro conditions; cultivar selection; optimized agronomic practices in a controlled cultivation environment; strategic manipulation of the light spectrum; topping; treatment with 6-benzylaminopurine (BAP); cultivar selection and water management; genetically uniform material under different environmental conditions. For greater success in increasing CBD without increasing THC, choosing a Chemotype III strain for medicinal purposes is paramount. DOI: https://doi.org/10.56238/sevened2026.008-112